Alignment of Question Types with Reading Comprehension Aspects - Alfiana, Septy Okta; Rochsantiningsih, Dewi; Drajati, Nur Arifah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study analyzes the alignment between question types in the grade X English textbook “Work in Progress” and aspects of reading comprehension. Using a content analysis technique, it investigates how these question types in reading tasks promote the five components of reading comprehension. The results suggest that WH Questions dominate, while Multiple Choice, Cloze Procedure, Skimming, and Scanning are absent, indicating a lack of diversity that may hamper the development of complete reading skills. Regarding reading comprehension aspects, the most frequently occurring aspects are determining the main idea and detailing information, while the aspects of locating references and making inferences tend to be underrepresented. The findings underline the need of incorporating a variety of question types into reading tasks to assist all elements of comprehension. This indicates that textbook authors and curriculum developers should provide resources that encourage a complete approach to improving students' reading abilities.